ANCHORS AND TENSIONER AND ANCHOR LOADING SYSTEMS FOR ACTIVE BONE AND JOINT STABILIZATION DEVICES - Powelson, Stephen; Castro, Carlos; Stecco, Kathryn A; Campbell, Damon Covell; Grinstead, Forrest (2021)
Implant tensioning and/or implant anchor deployment devices are described. Certain embodiments may be recognized in the form of a so-called tensioning "gun." Other embodiments take a simpler and more compact form. Various optional features are described in connection with these embodiments. Optional aspects of anchor embodiments for the subject implants are also described. Some of these features are coordinated for use with the implant tensioning and anchor deployment instrument, others are not.